Use of Intracytoplasmic Sperm Injection and Birth Outcomes in Women Conceiving through In Vitro Fertilization. Issue 2 (31st January 2017) - Xiong, Xu; Dickey, Richard P.; Buekens, Pierre; Shaffer, Jeffrey G.; Pridjian, Gabriella
Abstract: Background: Despite questionable evidence of benefits over conventional in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI) use has markedly increased in recent decades among couples without male factor infertility. We assessed the frequency of ICSI use and its effect on birth outcomes. Methods: A retrospective cohort study was conducted in 141 030 women conceiving through IVF using 2006–2010 data from the Society for Assisted Reproductive Technology (SART). Results: Between 2006 and 2010, overall ICSI use in women conceiving through IVF increased from 68.9% to 73.1%. This increase was greater among women without male factor infertility (53.0–59.2%) than in women with male factor infertility (92.0–93.4%). Women conceiving through IVF with and without ICSI had similar rates of multiple pregnancy, preterm delivery, stillbirth, and neonatal death. However, ICSI pregnancies were associated with an increased risk of birth defects over conventional IVF (3.0% for ICSI vs. 2.5% for conventional IVF; adjusted odds ratio (OR) 1.2, 95% confidence interval (CI) 1.2, 1.3). These increases were observed in both women conceiving through ICSI with male factor infertility (3.2% vs. 2.5%; OR 1.4, 95% CI 1.3, 1.5) and without male factor infertility (2.7% vs. 2.5%; OR 1.1, 95% CI 1.1, 1.2). Conclusions: Higher rates of birth defects were observed among women conceiving through ICSI. Since approximately half of all ICSI procedures are performed in couples without male factor infertility, ICSI may be overused in practice.